Acetylcholinesterase-like proteins are a major component of reproductive trail mucus in the invasive pest land snail, Theba pisana - Inaliguyau R. T. Lutschini; Kate R. Ballard; Tianfang Wang; Scott F. Cummins (PLoS ONE, 2025)
Invasive invertebrate pests have become a major threat to food security as global populations increase. Pesticides, often containing organophosphates, have long been used as agents for providing immediate short-term recovery, yet are often broad-spectrum, leading to the development of resistance. In insect species, one mechanism for resistance is known to be driven by mutations in acetylcholinesterase (AChE), an enzyme that catalyses the hydrolysis of acetylcholine. In this study, we explored a potential role for resistance-modified AChE in invasive pest land snails, using the Mediterranean snail Theba pisana. Following tissue transcriptomic investigation, an expanded family of AChE-like genes were identified that clustered phylogenetically into three individual clades, with one clade including vertebrate AChE. The majority of T. pisana AChE-like genes demonstrated the highest expression in the snail mucous gland during its reproductive stage. Subsequent proteomic analysis of trail mucus at the reproductive stage identified four AChE-like proteins as a major component. Immunolocalisation revealed that AChE-like protein(s) were prominent in the mucous gland secretory cells and widespread throughout the reproductive stage trail mucus, yet were largely absent from trail mucus at the non-reproductive stage. In summary, this study established a potential role for resistance-modified AChE-like proteins in pest land snail pesticide resistance via their deployment into trail mucus that may bio-scavenge organophosphates, rendering them ineffective. Their abundance during the reproductive stage is likely due to the snail’s increased mobility, following periods of immobile aestivation.